Optimization of Solution Condition for an Effective Electrochemical Reduction of N2O. Issue 4 (23rd January 2019) - Kwon, Oh Sung; Baek, Seungyeon; Kim, Hyeonsu; Choi, Insoo; Kwon, Oh Joong; Kim, Jae Jeong
Abstract: An effective electrochemical reduction of nitrous oxide (N2 O) is established by controlling solution compositions in this study. N2 O was electrochemically reduced varying solvent composition and supporting electrolytes (K2 SO4 and Na2 SO4 ) concentrations. The differences in reduction current density and solution resistance were analyzed via linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS), respectively, depending on solution conditions. UV‐Vis spectroscopy was adopted to measure the solubility of N2 O. As a result, among the conditions investigated in this study, 300 mM of K2 SO4 and aqueous based solution were revealed as an optimum condition for the electrochemical N2 O reduction. At 300 mM of K2 SO4, the highest current density was obtained due to a high conductance of the electrolyte and a moderate solubility of N2 O. Abstract :